INFORMATION SECURITY RISK MATURITY ASSESSMENT OF CENTRAL JAVA DATA CENTER BASED ON GOVERNMENT REGULATIONS AND ISO 27001:2022 - Fajar Andy Daniarta; Aji Supriyanto (Program Studi Teknik Informatika Universitas Khairun, 2026)
The increasing use of E-government (SPBE) has accelerated digital change in public administration but has also created real risks to information security. This study aims to evaluate the level of information security risk management maturity at the Central Java Provincial Data Center by merging the Indonesian SPBE Risk Management framework (PermenPANRB No. 5/2020) with SNI ISO/IEC 27001:2022. The evaluation utilized a descriptive qualitative method, backed by observations, interviews, and a survey-based maturity assessment that aligns with the control areas of ISO/IEC 27001. Findings reveal that the overall maturity sits between “Managed and Measurable” (Level 4) and “Optimized” (Level 5), indicating that most procedures are organized, documented, and consistently observed; however, some sub-controls still need enhancement, especially those related to incident response, ongoing improvement, and staff awareness. This research emphasizes the necessity for a more flexible security governance approach and contributes by integrating national regulatory guidelines with global information security frameworks to enhance the maturity assessment of government data centers.